Incidence and risk factors of deep vein thrombosis in patients with spinal cord injury: a systematic review with meta-analysis - Shang, Zhizhong; Wanyan, Pingping; Zhang, Baolin; Wang, Mingchuan; Wang, Xin (Frontiers in Cardiovascular Medicine, 2023)
Background Spinal cord injury (SCI) is a highly disabling disease with huge public health burden. The complications associated with it, especially deep vein thrombosis (DVT), further aggravate the disability. Objective To explore the incidence and risk factors of DVT after SCI, in order to provide guidance for disease prevention in the future. Methods A search was performed on PubMed, Web of science, Embase, and Cochrane database up to November 9, 2022. Literature screening, information extraction and quality evaluation were performed by two researchers. The data were later combined by metaprop and metan commands in STATA 16.0. Results A total of 101 articles were included, including 223,221 patients. Meta-analysis showed that the overall incidence of DVT was 9.3% (95% CI: 8.2% - 10.6%), and the incidence of DVT in patients with acute and chronic SCI was 10.9% (95% CI: 8.7% - 13.2%) and 5.3% (95% CI: 2.2% - 9.7%), respectively. The incidence of DVT decreased gradually with the accumulation of publication years and sample size. However, the annual incidence of DVT has increased since 2017. There are 24 kinds of risk factors that may contribute to the formation of DVT, involving multiple aspects of the baseline characteristics of the patient, biochemical indicators, severity of SCI, and comorbidities. Conclusions The incidence of DVT after SCI is high and has been gradually increasing in recent years. Moreover, there are numerous risk factors associated with DVT. Comprehensive preventive measures need to be taken as early as possible in the future.